2014
DOI: 10.4322/rbeb.2014.002
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Raman spectroscopy: determination of natural moisturizing factor profile related to skin hydration

Abstract: Introduction: Skin health and skin care to reduce the effects of aging are the main interests of many researchers.The skin is very important because it protects the body from various effects of the external environment, and studies of the largest organ of the human body have been conducted since antiquity. In skin, aging effects are severe enough to promote changes in cell structure and biochemical composition. In this study, we quantitatively analyzed the water content and natural moisturizing factor of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
2
2
0
Order By: Relevance
“…The concentrations of both isomers of UCA almost doubled in the SC treated with the emollient emulsion. Our results indicated that the application of the emollient sample, for 2 h, increased the UCA concentration in the outermost layers of the SC; these results agreed with the ones from Teixeira et al ( 2014), when the UCA was analyzed as a biomarker for the NMF under 30 days of cosmetic product use, and had an increase of 38.5% [25]. Total UCA concentration (the sum of the trans-and cis-UCA) from the SC samples generated a significant increase when the emollient emulsion was applied to the subjects' forearms in comparison to the non-treated SC (Wilcoxin matched-pairs signed rank test, two tailed, n = 12, α = 0.05) (Figure 2).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The concentrations of both isomers of UCA almost doubled in the SC treated with the emollient emulsion. Our results indicated that the application of the emollient sample, for 2 h, increased the UCA concentration in the outermost layers of the SC; these results agreed with the ones from Teixeira et al ( 2014), when the UCA was analyzed as a biomarker for the NMF under 30 days of cosmetic product use, and had an increase of 38.5% [25]. Total UCA concentration (the sum of the trans-and cis-UCA) from the SC samples generated a significant increase when the emollient emulsion was applied to the subjects' forearms in comparison to the non-treated SC (Wilcoxin matched-pairs signed rank test, two tailed, n = 12, α = 0.05) (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…The concentrations of both isomers of UCA almost doubled in the SC treated with the emollient emulsion. Our results indicated that the application of the emollient sample, for 2 h, increased the UCA concentration in the outermost layers of the SC; these results agreed with the ones from Teixeira et al ( 2014), when the UCA was analyzed as a biomarker for the NMF under 30 days of cosmetic product use, and had an increase of 38.5% [25]. The influence of artificial UV irradiation was also evaluated over the SC obtained by the tape stripping method.…”
Section: Resultssupporting
confidence: 91%
“…CRS was also used in vivo to observe the effects of antiage cosmetic products on the level of hydration and NMF. 15 The effects of the investigated products increased the level of hydration and enhanced NMF.…”
Section: Introductionmentioning
confidence: 95%
“…In vivo confocal Raman spectroscopy is a powerful non-invasive technique that allows an analysis of skin constituents [24][25][26][27][28][29] related to biochemical composition, permeation processes [27][28][29][30] of the skin and RA, and it can replace other methods such as skin biopsy and tape tripping [31,32].…”
Section: Introductionmentioning
confidence: 99%